A new insight into modelling the behaviour of unsaturated soils. (16th November 2012) - Arairo, Wahib; Prunier, Florent; Djéran‐Maigre, Irini; Darve, Félix
SUMMARY Understanding the response of partially saturated soils under different loads is important for the design and construction of economical and safe geotechnical engineering structures. This paper presents a coupled elastoplastic constitutive model for predicting the hydraulic and stress–strain–strength behaviour of unsaturated soils. The model proposed is built according to the following principle. A constitutive relation is given for each phase (solid, liquid and gas) and coupling relations between each phases are also derived. In the present case, we assume that each phase is not miscible and that pressure in voids not filled by water remains more or less constant, which is reasonable for most geotechnical problems. Therefore, the model is written in a classical manner with a non associated elastoplastic model for the granular skeleton behaviour; an incompressible liquid phase; a water retention description; and an assumption of the existence of an effective stress concept defined by Bishop. According to the strong hypotheses made earlier about the fluid phases, the perfect gas law is not written for the gas phase. Therefore, the gas volume is defined as being the same as the void volume not filled by water. The main originality of this work is in the description of the water retention behaviour and in that of the coupling parameter using the Bishop relationship. A discussion on this parameter and the description of the so called loading‐collapse phenomenon are provided. We demonstrate that this paradox can be explained without introducing suction in the expression of the plastic yield surface. Copyright © 2012 John Wiley & Sons, Ltd.